PERLINDUNGAN HUKUM TERHADAP KORBAN KONTAK DARURAT SEPIHAK DALAM PERJANJIAN PINJAMAN ONLINE WILAYAH POLRES SUKABUMI KOTA - Deani, Cintya; Sri Mulyanti, Asti (MAJALAH KEADILAN, 2024)
This study addresses the phenomenon of unilateral use of emergency contacts in online loans in Indonesia, which often involves emergency contacts without their consent. The use of unauthorized emergency contacts is a harmful practice that invades privacy and violates the rights of the individuals involved. The research method employed is a normative juridical approach with a descriptive-analytical approach, combining primary data from legal literature and secondary data from interviews and field research. The results of the study indicate that legal protection for victims who are unilaterally listed as emergency contacts is still inadequate. Although regulations govern the use of emergency contacts in online loan applications, their implementation remains ineffective. Legal consequences for violations of unauthorized emergency contact use need to be more firmly enforced and closely monitored by the Financial Services Authority (OJK) and law enforcement agencies. Based on the analysis, it was found that emergency contacts in online loan applications must involve explicit consent from the individuals concerned before they can be listed. Violations of this rule can result in severe administrative sanctions, including fines and revocation of operating licenses for non-compliant online loan providers. The study also highlights the responsibilities of the related parties, including online loan applications, debtors, and emergency contacts, in dispute resolution and individual rights protection. Legal efforts that can be undertaken by victims include filing lawsuits and reporting to authorities to enforce their rights and seek justice.